The Role of User Competence Moderation in the Influence of Management Information Systems on Performance - Naser, Ahmed; Hidayati, Nur; Pardiman, Pardiman (Fakultas Ekonomi, UIN Maliki Malang, 2025)
Abstract: This article aims to analyze how user competency moderates the performance of FEB lecturers in a management information system at the Islamic University of Malang. The research sample consists of 45 permanent lecturers. Questionnaires were distributed via Google Forms as direct data collection from respondents. The data were then analyzed using structural equation modeling partial least squares (SEM-PLS), which was then used to answer the research hypothesis. The results showed that both the management information system and user competence have a significant effect on lecturer performance. However, user competence does not moderate the influence of management information systems on lecturer performance. Implications for further research suggest comparing the performance of lecturers at other universities.